Sosialisasi dan Edukasi Hak Disabilitas melalui Program Mini Project Ramah Difabel di Desa Sidomulyo Kabupaten Sleman - Shabila Aulia; Fajar Noor (UNITY: Journal of Community Service, 2025)
Persons with disabilities often face barriers in gaining recognition and protection of their rights within society. The low level of public awareness remains a major obstacle to creating an inclusive and disability-friendly environment. This community service project aims to enhance awareness and understanding among residents of Sidomulyo Village, Sleman Regency, regarding the rights of persons with disabilities through a participatory mini project approach. The method consisted of initial observation, interactive socialization, development of educational media (posters and videos), and participatory evaluation. The results indicate a significant increase in public knowledge of disability rights, as evidenced by the pre- and post-activity questionnaire. Furthermore, a local resident group was formed to continue promoting inclusive education in the community. The mini project approach proved to be an effective and practical method for fostering community-based social awareness. It is hoped that this activity can be replicated in other regions with appropriate contextual adaptations.